Development of plasma probe platform for in-situ measurement with real-time communication system using sounding rocket - Zulkifli Abdul Aziz,; Siti Harwani Md. Yusoff, (Fakulti Kejuruteraan ,UKM,Bangi., 2024)
This paper presents the development of a plasma probe platform designed for in-situ measurements, complemented by a real-time communication system. The primary objective is to establish an integrated system that seamlessly merges a plasma probe platform with a dependable and efficient real-time communication infrastructure. The platform is equipped with a diverse array of sensors, including those for temperature, magnetic field, acceleration, camera imaging, pressure, and GPS positioning. This comprehensive sensor suite enhances our comprehension of the intricate relationship between in-situ plasma probe measurements and various environmental parameters. The real-time communication system plays a pivotal role in ensuring continuous and uninterrupted data transmission between the platform and the ground station operator throughout the data collection process. This enables valuable real-time access to the gathered data, facilitating immediate analysis and decision-making. Moreover, the real-time communication system serves as a fail-safe mechanism in case of recovery failure, guaranteeing that data can still be transmitted and monitored even if the platform encounters difficulties during retrieval. By adopting this integrated approach, researchers gain the capability to monitor, analyze, and derive insights from the collected data in real-time, even under challenging recovery scenarios. The development of this advanced plasma probe platform, coupled with the effective real-time communication system, significantly enhances our capacity to investigate plasma phenomena. These advancements hold substantial implications for space exploration, atmospheric research, and a wide range of scientific endeavors, paving the way for groundbreaking discoveries and advancements in our understanding of complex physical phenomena.